1990
DOI: 10.1152/ajpgi.1990.259.2.g300
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet-activating factor in ischemia/reperfusion-induced leukocyte adherence

Abstract: The objective of this study was to determine whether platelet-activating factor (PAF) mediates the leukocyte-endothelial cell interactions elicited by ischemia/reperfusion. The rates of adherence and extravasation of leukocytes were monitored in cat mesenteric venules subjected to 60 min of ischemia (blood flow reduced to 20% of control) followed by 60 min of reperfusion. Leukocyte rolling velocity, red blood cell velocity, and vessel diameter were also measured. The experiments were performed in control (untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
9

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 18 publications
2
91
0
9
Order By: Relevance
“…Indeed, certain effects of endothelin-1 can be attenuated by PAF receptor antagonists (Lagente et al, 1989;Takayashu et al, 1989;Terashita et al, 1989;Battistini et al, 1990;Filep et al, 1991), and endothelin-1-induced PAF synthesis has also been reported (Lopez-Farre et al, 1990 (Voelkel et al, 1986). It is also possible that the bioavailability of these antagonists is different (Kubes et al, 1990). Taken together, these findings suggest that PAF may be an important mediator of the action of endothelin-1 on vascular permeability.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, certain effects of endothelin-1 can be attenuated by PAF receptor antagonists (Lagente et al, 1989;Takayashu et al, 1989;Terashita et al, 1989;Battistini et al, 1990;Filep et al, 1991), and endothelin-1-induced PAF synthesis has also been reported (Lopez-Farre et al, 1990 (Voelkel et al, 1986). It is also possible that the bioavailability of these antagonists is different (Kubes et al, 1990). Taken together, these findings suggest that PAF may be an important mediator of the action of endothelin-1 on vascular permeability.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, activated platelets per se are also a source of reactive oxygen species (18,19). The platelet agonists platelet-activating factor and thrombin are also known to mediate I/R-induced leukocyte adhesion (14,27). Thrombin in particular is a potent activator of platelets leading to increased P-selectin expression (10).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous models of inflammation, PAF has been shown to act through its specific receptor on target cells, leading to elevated intracellular calcium levels followed by production of additional mediators and to changes in vascular permeability characteristic of the inflammatory involvement of the tissue. [27][28][29] In general terms, the involvement of the vascular endothelium in inflammatory responses has been carefully and extensively defined. 30 Endothelial cells have been shown to respond to a variety of stimuli leading to the synthesis and expression of regulators critical to recruitment of circulating immune cells to inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%